FRONTLINE: Jill Emberson: A lifetime of bearing witness to help others - Vivien Altman (Asia Pacific Network, 2020)
Jill Emberson, an award-winning Australian journalist of Tongan heritage died in 2019. She achieved national attention for her campaign to provide a voice for all women suffering from ovarian cancer and for more and fairer funding for ovarian cancer research. Through an analysis of her programmes and interviews with colleagues, this article focuses on Emberson’s journalism from daily news coverage of Aboriginal and Torres Strait Islander protests in 1982 for public radio to her Meet the Mob podcast series in 2014. It focuses on her significant radio documentaries on women in the Pacific for the ABCs’ feminist Coming Out Show (1986) and Ties that Bind, which was about Tonga, including the Tongan diaspora in Australia (2009). It argues that Emberson’s own journey to discover her cultural identity shaped her as a reflective journalist whose work was underpinned by a concern for social justice, marginalised communities, the impacts of colonisation and gender discrimination.